Pengaruh Persepsi Siswa Dan Sarana Prasarana BK Terhadap Minat Layanan Bimbingan Konseling - Mustamir, Mustamir; Leo Charli; Viktor Pandra (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to determine the influence of student perceptions and BK infrastructure on interest in guidance and counseling services at SMA Negeri 9 Lubuklinggau. The method used is quantitative with a population of 256 students and a sample of 38 students through simple random sampling techniques, analyzed using multiple linear regression, F test and coefficient of determination (R2). The results of the simultaneous test show that student perceptions and BK infrastructure have a significant effect on interest in BK services (sig. F = 0.001 < 0.05) with R² = 97.9%. Thus, both independent variables together provide a strong contribution to interest in guidance and counseling services. Therefore, it can be concluded that there is a significant influence between student perceptions and BK infrastructure on interest in guidance and counseling services at SMA Negeri 9 Lubuklinggau. Keywords: Counseling Facilities and Infrastructure, Interest in Counseling Guidance Services, Student Perceptions.